Pelatihan Desain Grafis Menggunakan Aplikasi Canva Bagi Santri Pondok Pesantren Miftahul Falah Ash-Shiddiqie Bandung - Wijana, Miki (Ma'soem University, 2025)
The graphic design training using the Canva application was provided to the students of Pondok Pesantren Miftahul Falah Ash-Shiddiqie Bandung to enhance their digital skills. The selection of this topic is based on the students' need to keep up with technological advancements, especially in the field of design, which is increasingly required in the modern world. The community service method used was practice-based training, where the students were introduced to the basics of graphic design and the use of Canva, followed by independent practice sessions supervised by instructors. The results of the training showed that the students were able to grasp the fundamentals of graphic design and utilize Canva to create simple visual content that can be used in pesantren activities or event promotions. In conclusion, this training is essential in equipping students with skills relevant to the digital age and opening new opportunities for them to create and contribute creatively in their environment.